2010
DOI: 10.1088/0031-9155/55/19/003
|View full text |Cite
|
Sign up to set email alerts
|

Numerical model of heat transfer in the human eye with consideration of fluid dynamics of the aqueous humour

Abstract: In this work we present a new 3D numerical model for heat transfer in the human eye, which takes into account the aqueous humour flow in the anterior chamber. We show that consideration of this phenomenon in the calculations alters the temperature distribution on the corneal and lens surfaces, without, however, noticeably changing their absolute values. The most notable effect is that the coolest area of the cornea moves at a point of 2 mm inferior to its geometric centre. The maximum velocity of the fluid in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
36
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 28 publications
6
36
0
1
Order By: Relevance
“…Karampatzakis and Samaras reported that aqueous humor flow in the anterior chamber had an important role in heat transfer using a 3D numerical model [18]. We need further study to clarify the relation between ocular heat conduction and aqueous humor convection.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Karampatzakis and Samaras reported that aqueous humor flow in the anterior chamber had an important role in heat transfer using a 3D numerical model [18]. We need further study to clarify the relation between ocular heat conduction and aqueous humor convection.…”
Section: Discussionmentioning
confidence: 94%
“…Fig. 4 shows temperature elevation by frequency (18,22,35,40 GHz, averages of 6-8 rabbits: 26.5 GHz, average of 16 rabbits) during exposure to 200 mW/cm 2 at 18 or 40 GHz. Elevation of the corneal temperature was the highest, followed by elevation of the lens temperature and then the vitreous temperature.…”
Section: Discussionmentioning
confidence: 99%
“…AH flow is primarily caused by thermally-induced buoyant forces and this induces natural convection that may affect the overall heat transfer phenomena inside the eye. Studies carried out by Ooi and Ng [15] and Karampatzakis and Samaras [16] have shown that models that take into account the natural convection phenomenon produce corneal surface temperature profiles that are asymmetrical about the geometrical center of the cornea. The temperature along the pupillary axis around the anterior segment of the eye is also increased.…”
Section: Introductionmentioning
confidence: 99%
“…In the early study of heat transfer in the eye [16][17][18][19], the AH was assumed to be stagnant. A 2D eye model developed by Ooi and Ng [20,21] and a 3D eye model developed by Karampatzakis and Samaras [22] considered the coupling of the AH flow and heat transfer in the eye. Their results suggested that AH natural convection has non-negligible influences on the temperature distribution in the anterior eye.…”
Section: Introductionmentioning
confidence: 99%